THE KINETIC STUDY OF THE LINKAGE ISOMERISM IN [Co (NH ) NO ] F COMPLEX (Journal of Sciences, Islamic Republic of Iran)
In this research project, the nitrito nitro isomerization of [Co (NH3)5No2]F2 complex has been studied. Isomerization of this complex in the solid state follows a first order kinetics. The rate of isomerization at different temperatures was determined using a Fourier Transform Lnfrared Spectrophotometer. ? and ? are calculated at 298 K. The infrared, visible and ultraviolet spectra of this compound are also reported